2016
DOI: 10.1002/anie.201609971
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Oscillatory Motion of a Self‐Propelled Motor Driven by Decomposition of H2O2 by Catalase

Abstract: A self-propelled motor driven by the enzymatic reaction of catalase adsorbed onto a filter paper floating on an aqueous solution of H O was used to study nonlinear behavior in the motor's motion. An increase in the concentration of H O resulted in a change from no motion to irregular oscillatory motion, periodic oscillatory motion, and continuous motion. The mechanisms underlying oscillation and mode bifurcation are discussed based on experimental results on O bubble formation and growth on the underside of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…[1][2][3][4][95][96][97][98][99][100][101] Most of these studies focus on miniaturization likem icromotors and functionalization such as aJ anus particle. [102] At the interface of catalase paper and H 2 O 2 aqueous solution,a ne nzymatic reaction occurs. [102,103] When af ilter paper containing catalase is placed on aH 2 O 2 aqueouss olution, three types motion,t hat is, irregular oscillation, periodic oscillation, and continuousm otion occur at lower,m iddle, and higher concentrationso fH 2 O 2 ,r espectively.…”
Section: Coupling With Enzymatic Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][95][96][97][98][99][100][101] Most of these studies focus on miniaturization likem icromotors and functionalization such as aJ anus particle. [102] At the interface of catalase paper and H 2 O 2 aqueous solution,a ne nzymatic reaction occurs. [102,103] When af ilter paper containing catalase is placed on aH 2 O 2 aqueouss olution, three types motion,t hat is, irregular oscillation, periodic oscillation, and continuousm otion occur at lower,m iddle, and higher concentrationso fH 2 O 2 ,r espectively.…”
Section: Coupling With Enzymatic Reactionsmentioning
confidence: 99%
“…Recently,s elf-propelled objects driven by decomposition of H 2 O 2 were extended to exhibit nonlinearb ehavior in their motions. [102,103] When af ilter paper containing catalase is placed on aH 2 O 2 aqueouss olution, three types motion,t hat is, irregular oscillation, periodic oscillation, and continuousm otion occur at lower,m iddle, and higher concentrationso fH 2 O 2 ,r espectively. [102] At the interface of catalase paper and H 2 O 2 aqueous solution,a ne nzymatic reaction occurs.…”
Section: Coupling With Enzymatic Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanometer- to millimeter-sized objects undergoing spontaneous directional motion, deformation, or topological changes, generically classified as active matter 1 , 2 , are expected to find a broad range of applications in the miniaturization of many devices. In such systems, energy is supplied to the moving object by an external source 3 or by making it interact with its surroundings 4 , 5 . Drops spreading on a liquid substrate may fall into the second category when surface tension gradients take place, owing to phase change or to the presence of surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…Autonomous trajectories of micromotors can be controlled by the balance of motive–drag forces, shapes and geometrical asymmetry [ 102 , 103 ], effect of catalyst distribution [ 104 ], gravitaxis and separation phenomena for mass-anisotropic self-propelling colloids [ 105 ]. Interesting observations of periodic oscillatory motion driven by decomposition of H 2 O 2 using catalase was reported [ 106 ]. Several groups observed that catalytic nanorods could spontaneously turn and tumble, which is similar to swimming of bacteria.…”
Section: New Materials Geometries and Fuels For Autonomous Motionmentioning
confidence: 99%